Preservation of Postvaccinal Immunity to Measles, Rubella, Parotitis, Hepatitis B and Diphtheria in Patients With Juvenile Idiopathic Arthritis Who Undergone Planned Immunization Under the Age of Two: Preliminary Results of Cross-Sectional Study - Natalia A. Lybimova; Irina V. Fridman; Olga V. Goleva; Lubov S. Sorokina; Rinat K. Raupov; Rena V. Idrisova; Susanna M. Kharit; Mikhail M. Kostik (Вопросы современной педиатрии, 2020)
Background. Patients with juvenile idiopathic arthritis (JIA) can have low levels of antibodies to vaccine antigens due to immunologic features of the main disease, disruptions in vaccination schedule and immunosuppressive drugs administrationObjective. The aim of the study was to examine the status of postvaccinal immunity and determine the factors associated with preservation of protective level of antibodies in patients with JIA.Methods. This cross-sectional study included patients with JIA at the age from 2 to 17 years old vaccinated under the age of two (before JIA) against measles, rubella, parotitis, hepatitis B and diphtheria. Levels of IgG to vaccine antigens were measured by enzyme immunoassay. The minimum protective level of anti-measles IgG was esteemed as 0.18 IU/ml, antibodies to rubella — 10 IU/ml, for parotitis — COI > 1.0, for hepatitis B — 10 mIU/ml, antibodies to diphtheria — 0.09 IU/ml.Results. The study included 90 patients with JIA (71% of girls) at the age (median) 11.3 (7.5; 14.9) years. The age of JIA manifestation was 6.0 (4.0; 8.0) years, disease duration — 4.0 (2.0; 7.3) years. Glucocorticosteroids administration in anamnesis or at study entry was recorded in 24/88 (27%) patients, methotrexate — 81/88 (92%), genetically engineered biologic drugs — 54/89 (61%). Protective level of antibodies to measles virus was revealed in 45 (50%) children with JIA, to rubella virus — in 88 (98%), to parotitis — in 68 (76%), to hepatitis B — in 49 (54%), to diphtherial anatoxin — in 45 (50%). The decrease of postvaccinal immunity level was associated with JIA duration and glucocorticosteroids administration (against diphtheria) duration, as well as drop-out immunization (against measles).Conclusion. Major part of children with JIA have no protection against measles, parotitis, hepatitis B or diphtheria. High risk of progression of such vaccine-preventable diseases in these children demands development of individual programs of immunization.